2021
DOI: 10.1186/s12894-020-00775-3
|View full text |Cite
|
Sign up to set email alerts
|

Role of microRNA-381 in bladder cancer growth and metastasis with the involvement of BMI1 and the Rho/ROCK axis

Abstract: Background Emerging evidence has noted the important participation of microRNAs (miRNAs) in several human diseases including cancer. This research was launched to probe the function of miR-381 in bladder cancer (BCa) progression. Methods Twenty-eight patients with primary BCa were included in this study. Cancer tissues and the adjacent normal tissues were obtained. Aberrantly expressed miRNAs in BCa tissues were analyzed using miRNA microarrays. mi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 36 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…For example, dendrobine suppressed the endoplasmic reticulum stress-induced apoptosis by increasing miR-381-3p expression in endothelial cells [ 38 ]. Previously, miR-381 was reported to suppress cell proliferation and metastasis by targeting the BM1 and Rho/ROCK axis in bladder cancer [ 40 ]. Additionally, miR-381 facilitates autophagy and apoptosis by suppressing the RELN-mediated PI3K/Akt pathway in prostate cancer cells [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, dendrobine suppressed the endoplasmic reticulum stress-induced apoptosis by increasing miR-381-3p expression in endothelial cells [ 38 ]. Previously, miR-381 was reported to suppress cell proliferation and metastasis by targeting the BM1 and Rho/ROCK axis in bladder cancer [ 40 ]. Additionally, miR-381 facilitates autophagy and apoptosis by suppressing the RELN-mediated PI3K/Akt pathway in prostate cancer cells [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The tumor-suppressing properties of miR-381was shown to be blocked by overexpression of BMI. Overexpression of miR-381 decreased RhoA phosphorylation and Rho-associated protein kinase (ROCK2) activation ( Chen et al, 2021a ). miRNA-145 was significantly downregulated in patients with bladder cancer.…”
Section: Mirna and Bladder Cancermentioning
confidence: 99%
“…MicroRNAs (miRNAs) have been proven to be one of the most common endogenous noncoding RNAs, which can bind to the 3′ noncoding sequence of particular messenger RNAs (mRNAs) to modulate their translational performance and stability [ 5 ]. Recently, a good deal of investigations has indicated that abnormal changes of miRNAs partake in the regulation of the occurrence and development of different types of human malignancies and are associated with cell development, cell proliferation, apoptosis, and tumorigenesis [ 6 8 ]. Thus, miRNAs are considered to be outstanding biomarkers for the diagnostic analysis, targeting therapy, and prediction of malignant tumors.…”
Section: Introductionmentioning
confidence: 99%